The Brassicaceae Family in Huaylas Province, Ancash - Monsalve, Christhian (2003)
A total of 25 species were found in the study area grouped in 12 genera and 5 tribes. Eight species are considered additions to the flora for the department of Ancash. None of the species reported as endemic for Ancash were found. Dichotomous keys are presented for the genera and some species. A brief description and information on the ecology and distribution of each species is included as well as the exicatta.